Guidelines for the Rational Design and Engineering of 3D Manufactured Solid Oxide Fuel Cell Composite Electrodes. Issue 2 (14th December 2016) - Bertei, A.; Tariq, F.; Yufit, V.; Ruiz-Trejo, E.; Brandon, N. P.
Abstract : The growth of 3D printing has opened the scope for designing microstructures for solid oxide fuel cells (SOFCs) with improved power density and lifetime. This technique can introduce structural modifications at a scale larger than particle size but smaller than cell size, such as by inserting electrolyte pillars of ∼5–100 μm. This study sets the minimum requirements for the rational design of 3D printed electrodes based on an electrochemical model and analytical solutions for functional layers with negligible electronic resistance and no mixed conduction. Results show that this structural modification enhances the power density when the ratio keff between effective conductivity and bulk conductivity of the ionic phase is smaller than 0.5. The maximum performance improvement is predicted as a function of keff . A design study on a wide range of pillar shapes indicates that improvements are achieved by any structural modification which provides ionic conduction up to a characteristic thickness ∼10–40 μm without removing active volume at the electrolyte interface. The best performance is reached for thin (<∼2 μm) and long (>∼80 μm) pillars when the composite electrode is optimised for maximum three-phase boundary density, pointing toward the design of scaffolds with well-defined geometry and fractal structures.